On the biological properties of alkynyl phosphine gold(I) complexes - Meyer, Andreas; Alborzinia, Hamed; Can, Suzan; Wölfl, Stefan (Angewandte Chemie. International edition, 2012)
Golden times for metal-based drugs? Alkynyl triphenylphosphine gold(I) complexes display interesting biological properties and show high potential for future drug development. They are strong inhibitors of the enzyme thioredoxin reductase, trigger antiproliferative effects in tumor cells, and influence tumor cell metabolism, mitochondrial respiration, and angiogenesis in zebrafish embryos.